Carbon dots and miniaturizing fabrication of portable carbon dot-based devices for bioimaging, biosensing, heavy metal detection and drug delivery applications. Issue 41 (13th October 2022) - Yat, Yu Dong; Foo, Henry Chee Yew; Tan, Inn Shi; Lam, Man Kee; Lim, Steven
Abstract : Adopting the additive and subtractive fabrication techniques to integrate miniaturized portable devices with carbon dots for on-site and real-time analysis. Abstract : Carbon dots (CDs), classified as quasi-spherical carbonaceous nanoparticles, have recently gained much attention in wastewater treatment. Their superior distinctive properties, such as non-toxicity, biocompatibility and optical properties, make them a promising option compared to the conventional inorganic semiconductor quantum dots. Herein, the recent progress in CD synthesis methods and photoluminescence properties have been highlighted. Besides, the tailoring process of photoluminescence via surface functionalization is presented. Most importantly, this review aims to provide insightful knowledge on the advanced techniques to fabricate miniaturized CD-based sensing platforms for on-site and real-time analysis. These techniques can be divided into two main paths, i.e., the additive and subtractive methods as well as the combination of both with the illustration of graphical diagrams. Further, the applications of CDs in bioimaging, biosensing, heavy metal detection and drug delivery are elaborated based on the current progress of the experimental works. Lastly, the future perspective and challenges to develop and utilize the CDs are discussed accordingly. In short, this review tends to promote more research on the connection between online networks and the miniaturized property of CDs in enhancing on-site and real-time applications.